1994
DOI: 10.1021/ac00082a008
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Modeling, Prediction, and Multifactor Optimization in Micellar Electrokinetic Chromatography of Ionizable Compounds

Abstract: Previously, the use of phenomenological models to describe the migration behavior of acidic solutes in micellar electrokinetic chromatography (MEKC) was reported. In this paper, the phenomenological approach is further extended by including both acidic and basic solutes and simultaneously taking two important experimental factors (pH and micelle concentration) into consideration. In addition, a general method is described to model the migration behavior of ionizable (both acidic and basic) solutes in MEKC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Here data on the pH dependence of the distribution coefficient as a function of pH are usually not available. A recent publication [10] reported on computerassisted modelling of MECC of ionizable compounds. Distribution coefficients of ionized and non-ionized forms were determined.…”
Section: Vmi C ~" (Iltmi C + ~T£eof)e (7)mentioning
confidence: 99%
“…Here data on the pH dependence of the distribution coefficient as a function of pH are usually not available. A recent publication [10] reported on computerassisted modelling of MECC of ionizable compounds. Distribution coefficients of ionized and non-ionized forms were determined.…”
Section: Vmi C ~" (Iltmi C + ~T£eof)e (7)mentioning
confidence: 99%
“…In recent years, in order to predict the optimal separation conditions with the minimum number of experiments, several strategies in MEKC have been reported [1,2]. As an example, it can be cited the overlapping resolution mapping (ORM) [3][4][5][6][7][8][9], iterative regression strategies [10], physicochemical approaches [11][12][13][14], empirical equations [15][16][17][18], and artificial neural networks (ANNs) [19]. In order to carry out these studies, several designs can be used, e.g., the Plackett-Burman design [20,21] and the orthogonal array design (OAD) [22] which are factorial designs suitable for screening the influence of many parameters and to monitor possible interactions among a large number of factors, or the central composite design [23,24] that can provide a response surface for the prediction of areas of optimum performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Khaledi et al [11][12][13][14] introduced physicochemical models describing the migration behavior of both acidic and basic solutes as a function of the separation buffer composition and physicochemical constants. First, a description of migration in terms of pK a , micelle-water binding constant, and mobility of the anionic solutes in the absence of micelles has been performed [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the migration behaviour has been studied extensively and several models have been reported that describe migration in terms of physico-chemical constants, such as micelle binding constants and apparent dissociation constants in micellar media [7][8][9][10][11]. In this work, the mobility and retention models |or monovalent weak acids in an anionic micellar system are evaluated and compared.…”
Section: Introductionmentioning
confidence: 99%